Percutaneous kyphoplasty for the treatment of diffuse idiopathic skeletal hyperostosis with vertebral fractures: A case report and treatment review - Wang, Wenhao; Huang, Yixue; Zhang, Linlin; Yang, Huilin (Frontiers in Surgery, 2022)
Diffuse idiopathic skeletal hyperostosis (DISH) is a systemic metabolic condition characterized by new bone formation mainly at the anterolateral spine. Surgery such as screw fixation is commonly used for DISH patients who also suffer from vertebral fractures. In this case report, we share a DISH case with lumbar vertebral fracture and osteoporosis who underwent percutaneous kyphoplasty plus braces and medication. Percutaneous kyphoplasty, considered as minimally invasive surgery, may be another treatment option with the advantages of less trauma and faster recovery. The clinical information and radiological findings are described and treatments for DISH with vertebral fractures are then briefly reviewed.